Knowledge, Attitude, and Practices of English Teachers in Utilizing Integrative Performance Tasks in English - Aquino, Khate Giselle G; Rufino, Mark Clester A; Paguirigan, Elgin S; Cruz-Vidal, Michaela Jennarine DL (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The study “Knowledge, Attitude and Practices of English Teachers in Utilizing Integrative Performance Tasks in English” described and then analyzed the knowledge, attitude and practices of English teachers in designing and utilizing Integrative Performance Task in the New Normal Education. To achieve this aim, the researcher used a sample of 50 English Senior and Junior High School public school teachers in Talavera, Nueva Ecija. The researcher used the descriptive-correlational method of research, which utilized a researcher-made questionnaire to gather the data needed for the study. The findings showed that the majority of the teacher-respondents of Junior and Senior High Schools of Talavera, Nueva Ecija are Teacher III with previously earned units in Master's Degree who are handling Grade 10 students. Additionally, most of them are female, single, and between the ages of 23 and 29. Furthermore, the result shows that there was no significant relationship found between the profile of the respondents and their knowledge, attitude, and practices in using integrative performance tasks. Moreover, it showed that the teacher-respondents’ Highest Educational Attainment and Grade Level Taught significantly correlated with their Individual Performance Commitment and Review (IPCR) ratings. Lastly, it was found to have no significant relationship between the teachers’ utilization of Integrative Performance Task (IPT) in terms of their knowledge, attitude, and practices and their Individual Performance Commitment and Review (IPCR) ratings. Conclusions were drawn based on the findings of the study and recommendations were presented and offered.